Understanding and Communicating about COVID-19 Vaccine Efficacy, Effectiveness, and Equity - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Effective communication is needed to ensure shared understanding of how well COVID-19 vaccines work and whether they are being equitably distributed. Without clear, consistent, readily accessible communications, people may lose faith in the vaccines and in those providing them. State, tribal, local, and territorial officials can play a key role in conveying that information to community members or intermediaries in a timely, clear, authoritative way and in conveying community concerns to policy makers. This rapid expert consultation summarizes social, behavioral, and decision science research relevant to communicating how well COVID-19 vaccines work are and how equitably they are being distributed. It offers practical strategies for both the process and the content of such communication, recognizing that people respond to both how they learn about something and what they learn about it. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats, sponsored by the U.S. Department of Health and Human Services, Office of the Assistant Secretary for Preparedness and Response.

Space Radiation and Astronaut Health: Managing and Communicating Cancer Risks - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Astronauts face unique health-related risks during crewed space missions, and longer-duration missions that extend to greater distances in our solar system (including to the Moon and Mars) will likely increase those risks. Cancer risks due to ionizing radiation exposure are one of these health-related risks. Assessing, managing, and communicating radiation-induced cancer risks associated with spaceflight are challenging because of incomplete knowledge of the radiation environment in space, limited data on radiation-induced cellular damage mechanisms, lack of direct observations from epidemiological studies, and the complexities of understanding radiation risk. At the request of the National Aeronautics and Space Administration (NASA), an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine convened to provide advice on NASA's proposed updates to their space radiation health standard, which sets the allowable limit of space radiation exposure throughout the course of an astronaut's career. Space Radiation and Astronaut Health: Managing and Communicating Cancer Risks provides the committee's recommendations and conclusions regarding the updated space radiation health standard, NASA's radiation risk communication strategies, and a process for developing an ethics-informed waiver protocol for long-duration spaceflight missions.

Communication Strategies for Building Confidence in COVID-19 Vaccines: Addressing Variants and Childhood Vaccinations - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
The fourth wave of the COVID-19 pandemic in the United States has been fueled by the delta variant, which is more contagious than earlier variants, and a slowing down in new vaccinations. Most hospitalizations and deaths in the United States are occurring among people who are not vaccinated. This context affirms the importance of tackling vaccine hesitancy and communicating with parents of children who are eligible to be vaccinated and those for whom future eligibility is anticipated. This rapid expert consultation identifies actionable guidance that state and local decision makers can use to communicate with the public to build confidence in and promote the uptake of COVID-19 vaccines. This rapid expert consultation was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation and the Alfred P. Sloan Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is affiliated with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats and the Standing Committee on Advancing Science Communication.

Communicating Clearly About Medicines: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Research conducted over the past two decades has shown that poor patient understanding of medication instructions is an important contributor to the more than 1 million medication errors and adverse drug events that lead to office and emergency room visits, hospitalizations, and even death. Patients who have limited literacy skills, who have multiple comorbidities, and who are elderly face the greatest risk, and limited literacy skills are significantly associated with inadequate understanding and use of prescription instructions and precautions. The Agency for Healthcare Research and Quality notes that only 12 percent of U.S. adults have proficient health literacy that allows them to interpret a prescription label correctly. Given the importance of health literacy to the proper use of medications, and the apparent lack of progress in improving medication adherence, the Roundtable on Health Literacy formed an ad hoc committee to plan and conduct a 1-day public workshop that featured invited presentations and discussion of the role and challenges regarding clarity of communication on medication. Participants focused on using health literacy principles to address clarity of materials, decision aids, and other supportive tools and technologies regarding risks, benefits, alternatives, and health plan coverage. This publication summarizes the presentations and discussions from the workshop.

Communicating Clearly About Medicines: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
On November 17, 2016, the Roundtable on Health Literacy of the National Academies of Sciences, Engineering, and Medicine convened a workshop on communicating clearly about medicines. The workshop focused on the clarity of written information given to patients and consumers as printed or digital materials. Participants explored the design of health-literate written materials and examples that illustrated implementation of research into the development of these materials. This publication summarizes the presentations and discussions from the workshop.

Building Communication Capacity to Counter Infectious Disease Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
Building communication capacity is a critical piece of preparing for, detecting, and responding to infectious disease threats. The International Health Regulations (IHR) establish risk communication2014the real-time exchange of information, advice, and opinions between experts or officials and people who face a threat to their survival, health, and economic or social well-being2014as a core capacity that World Health Organization member states must fulfill to strengthen the fight against these threats. Despite global recognition of the importance of complying with IHR, 67 percent of signatory countries report themselves as not compliant. By investing in communication capacity, public health and government officials and civil society organizations facing health crises would be prepared to provide advice, information, and reassurance to the public as well as to rapidly develop messages and community engagement activities that are coordinated and take into account social and behavioral dynamics among all sectors. To learn about current national and international efforts to develop the capacity to communicate effectively during times of infectious disease outbreaks, and to explore gaps in the research agenda that may help address communication needs to advance the field, the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine convened a 1.5 day workshop on December 13 and 14, 2016, in Washington, DC. Participants reviewed progress and needs in strengthening communication capacity for dealing with infectious disease threats for both outbreaks and routine challenges in the United States and abroad. This publication summarizes the presentations and discussions from the workshop.

Health Communication with Immigrants, Refugees, and Migrant Workers: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2017)
In March 2017, the Roundtable on Health Literacy of the National Academies of Sciences, Engineering, and Medicine convened a workshop focused on health communication with people from immigrant, refugee, and migrant worker populations. The workshop was organized to explore the application of health literacy insights to the issues and challenges associated with addressing the health of immigrants, refugees, and migrant workers. Participants explored issues of access and services for these populations as well as outreach and action. This publication summarizes the presentations and discussions from the workshop.

Health Literacy and Communication Strategies in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2020)
Health literacy is a critical skill for engaging in healthy behaviors to reduce disease risk and improve health outcomes across the continuum of cancer care. However, estimates suggest that more than one-third of the U.S. adult population has low health literacy, and nearly half of all patients with cancer have difficulty understanding information about their disease or treatment. Low health literacy among patients with cancer is associated with poor health and treatment outcomes, including lower adherence to treatment, higher rates of missed appointments, and an increased risk of hospitalization. Low health literacy can also impede informed decision making, especially as cancer care becomes increasingly complex and as patients and their families take more active roles in treatment decisions. To examine opportunities to improve communication across the cancer care continuum, the National Cancer Policy Forum collaborated with the Roundtable on Health Literacy to host a workshop, Health Literacy and Communication Strategies in Oncology, July 15-16, 2019, in Washington, DC. Patients, patient advocates, clinicians, and researchers, representatives of health care organizations, academic medical centers, insurers, and federal agencies explored the challenges of achieving effective communication in cancer care. This publication summarizes the presentations and discussions of the workshop.

Health Systems Science Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
The National Academies Global Forum on Innovations in Health Professional Education held a public workshop in November 2023. Speakers explored how health professional educators and providers with health systems science (HSS) training can prepare learners to work together within health systems, resulting in better patient care, improved population health, and enhanced health professional well-being. Organizers hosted a public pre-workshop in October 2023 to create a foundational understanding of HSS prior to their workshop.

Nonhuman Primate Models in Biomedical Research: State of the Science and Future Needs - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Nonhuman primates represent a small fraction of animals used in biomedical research, but they remain important research models due to their similarities to humans with respect to genetic makeup, anatomy, physiology, and behavior. Limitations in the availability of nonhuman primates have been exacerbated by the COVID-19 pandemic and recent restrictions on their exportation and transportation, impacting National Institutes of Health (NIH)-funded research necessary for both public health and national security. Additionally, there is continued interest in understanding whether and how nonanimal models can be used to answer scientific questions for which nonhuman primates are currently used. At the direction of the U.S. Congress, NIH asked the National Academies of Sciences, Engineering, and Medicine to convene an expert committee to conduct a landscape analysis of current and future use of nonhuman primates in NIH-supported biomedical research, as well as opportunities for new approach methodologies to complement or reduce reliance on nonhuman primate models. This report provides the committee findings and conclusions.

Communications and Technology for Violence Prevention: Workshop Summary - Institute of Medicine; National Research Council
In the last 25 years, a major shift has occurred in the field of violence prevention, from the assumption that violence is inevitable to the realization that violence is preventable. As we learn more about what works to reduce violence, the challenge facing those who work in the field is how to use all of this new information to rapidly deploy or enhance new programs. At the same time, new communications technologies and distribution channels have altered traditional means of communications, and have made community-based efforts to prevent violence possible by making information readily available. How can these new technologies be successfully applied to the field of violence prevention? On December 8-9, 2011, the IOM's Forum on Global Violence Prevention held a workshop to explore the intersection of violence prevention and information and communications technology. The workshop - called \

Facilitating State Health Exchange Communication Through the Use of Health Literate Practices: Workshop Summary - Institute of Medicine
Implementation of the Affordable Care Act (ACA) of 2010 will result in significant changes to the U.S. health care system. Among its many provisions, the ACA will extend access to health care coverage to millions of Americans who have been previously uninsured. Many of the newly eligible health insurance consumers will be individuals of low health literacy, some speakers of English and others more comfortable using languages other than English. Health insurance terms such as \

Perspectives on Research with H5N1 Avian Influenza: Scientific Inquiry, Communication, Controversy: Summary of a Workshop - Institute of Medicine; National Research Council (The National Academies Press, 2013)
When, in late 2011, it became public knowledge that two research groups had submitted for publication manuscripts that reported on their work on mammalian transmissibility of a lethal H5N1 avian influenza strain, the information caused an international debate about the appropriateness and communication of the researchers' work, the risks associated with the work, partial or complete censorship of scientific publications, and dual-use research of concern in general. Recognizing that the H5N1 research is only the most recent scientific activity subject to widespread attention due to safety and security concerns, on May 1, 2012, the National Research Council's Committee on Science, Technology and Law, in conjunction with the Board on Life Sciences and the Institute of Medicine's Forum on Microbial Threats, convened a one-day public workshop for the purposes of 1) discussing the H5N1 controversy; 2) considering responses by the National Institute of Allergy and Infectious Diseases (NIAID), which had funded this research, the World Health Organization, the U.S. National Science Advisory Board for Biosecurity (NSABB), scientific publishers, and members of the international research community; and 3) providing a forum wherein the concerns and interests of the broader community of stakeholders, including policy makers, biosafety and biosecurity experts, non-governmental organizations, international organizations, and the general public might be articulated. Perspectives on Research with H5N1 Avian Influenza: Scientific Enquiry, Communication, Controversy summarizes the proceedings of the workshop.

Communicating to Advance the Public's Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
The Institute of Medicine's Roundtable on Population Health Improvement brings together individuals and organizations that represent different sectors in a dialogue about what is needed to improve population health. On September 22, 2014, the roundtable held a workshop to discuss some of the science of health communication, audiences, and messaging, and to explore what it will take to generate widespread awareness, acceptance, and action to improve health, including through the entertainment media, the news media, and social media. This report summarizes the presentations and discussion of the workshop.

Food Literacy: How Do Communications and Marketing Impact Consumer Knowledge, Skills, and Behavior? Workshop Summary - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2016)
In September 2015, the National Academies of Sciences, Engineering, and Medicine's Food and Nutrition Board convened a workshop in Washington, DC, to discuss how communications and marketing impact consumer knowledge, skills, and behavior around food, nutrition, and healthy eating. The workshop was divided into three sessions, each with specific goals that were developed by the planning committee: Session 1 described the current state of the science concerning the role of consumer education, health communications and marketing, commercial brand marketing, health literacy, and other forms of communication in affecting consumer knowledge, skills, and behavior with respect to food safety, nutrition, and other health matters. Session 2 explored how scientific information is communicated, including the credibility of the source and of the communicator, the clarity and usability of the information, misconceptions\/misinformation, and the impact of scientific communication on policy makers and the role of policy as a macro-level channel of communication. Session 3 explored the current state of the science concerning how food literacy can be strengthened through communication tools and strategies. This report summarizes the presentations and discussions from the workshop.

Food Literacy: How Do Communications and Marketing Impact Consumer Knowledge, Skills, and Behavior? Workshop in Brief - Institute of Medicine; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2015)
On September 3-4, 2015, the Institute of Medicine Food and Nutrition Board convened a workshop to discuss how communications and marketing impact consumer knowledge, skills, and behavior around food nutrition, and healthy eating. The workshop goals developed by the planning committee were to: (1) describe the current state of the science concerning the role that consumer education, health communications and marketing, and other forms of communication play in affecting consumer knowledge with respect to food safety, nutrition, and other health matters; (2) explore how scientific information is communicated, including the credibility of the source and of the communicator, and the clarity and usability of information; and (3) explore the current state of the science concerning how food literacy can be strengthened through communications tools and strategies. This report highlights key points made by individual speakers and summarizes the workshop presentations and discussions.

Mitigating Health Disparities in Brain Disorders Starting with Basic Science: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2024)
Despite increased attention paid to health equity in recent years, disparities in health outcomes and access to care persist across disease areas, including in central nervous system disorders. The National Academies Forum on Neuroscience and Nervous System Disorders hosted a public workshop in November 2023 to reflect on strategies to advance equitable practices in neuroscience and improve data quality by engaging more diverse populations in the research process; acknowledging systematic, technological, and internal biases; and considering inclusive research models.

Exploring the Use and Application of Implementation Science in Health Professions Education: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2023)
Implementation science bridges the gap between research and medical practice, investigating aspects of practice and pedagogy that make the strategies successful for future use. By introducing and training leaders, faculty, and health workforce researchers in implementation science, health professions education institutions can build capacity for evidence-based practices. The National Academies Global Forum on Innovation in Health Professional Education held a workshop series to introduce the concept of implementation science to health professional educators to consider its potential use in the classroom. Speakers provided a foundation for discussion of the role of implementation science in health professions education and provided methods for educators interested in applying these recommendations to scale. This Proceedings of a Workshop highlights the presentations and discussions that occurred at the workshop.

Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Recent events, including the COVID-19 pandemic and the collective awakening around issues related to racial justice, diversity, and inclusion, have underscored the challenges facing neuroscience and neuroscience training. To address these challenges, the Forum on Neuroscience and Nervous System Disorders of the National Academies of Sciences, Engineering, and Medicine convened a series of virtual workshops on neuroscience training with the goal of reconsidering how we think about neuroscience training in a rapidly changing world. On February 22, 2021, the fifth and final workshop in this series, titled Evolving the Culture of Science and Training in Neuroscience to Meet a Changing World, brought together stakeholders from across the neuroscience ecosystem to discuss how the culture of science and scientific training can become more inclusive, balanced, and adaptive to changing times. This final workshop expanded on many issues raised in previous workshops, including the importance of mental health and well-being in academic research; how to resist the legacy of white supremacy and support diversity in academia; and how to redefine what success means for neuroscientists in both academic and non-academic settings. This publication summarizes the discussions that occurred at the workshop.

The Emerging Field of Human Neural Organoids, Transplants, and Chimeras: Science, Ethics, and Governance - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2021)
Each year, tens of millions of individuals in the U.S. suffer from neurological and psychiatric disorders including neurodegenerative diseases such as Alzheimer's Disease and Parkinson's Disease, and psychiatric disorders such as autism spectrum disorder, depression and schizophrenia. Treatments for these diseases are often completely lacking or only partially effective, due in large part to the difficulty of conducting brain research and the complexity of the brain itself. Researchers in recent years have developed new models to better represent and study the human brain. The three models considered in this report, all of which generate and use pluripotent stem cells from healthy individuals and patients, are human neural organoids, human neural transplants, and human-animal neural chimeras. The Emerging Field of Human Neural Organoids, Transplants, and Chimeras: Science, Ethics, and Governance reviews the status of research, considers its benefits and risks, discusses associated ethical issues, and considers governance mechanisms for this type of research.